2018
DOI: 10.1186/s13045-018-0604-6
|View full text |Cite
|
Sign up to set email alerts
|

First pediatric experience of SL-401, a CD123-targeted therapy, in patients with blastic plasmacytoid dendritic cell neoplasm: report of three cases

Abstract: BackgroundBlastic plasmacytoid dendritic cell neoplasm (BPDCN) is a highly aggressive hematological malignancy with extremely poor outcome. The median overall survival for adult patients is 9–13 months. Pediatric patients are exceedingly rare with an unclear clinical course. Currently, no standardized therapy has been established, although an acute lymphoblastic leukemia type of treatment appears to be more effective in those patients who are able to tolerate aggressive chemotherapy. SL-401 is a targeted thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 14 publications
0
32
0
Order By: Relevance
“…SL-401 was also tested in few pediatric BPDCN patients, providing preliminary evidence of clinical activity [99].…”
Section: Therapeutic Cd123 Targetingmentioning
confidence: 99%
“…SL-401 was also tested in few pediatric BPDCN patients, providing preliminary evidence of clinical activity [99].…”
Section: Therapeutic Cd123 Targetingmentioning
confidence: 99%
“…Sun et al from the City of Hope reported the first three cases of pediatric patients with this type of malignancy. Overall, the treatment was very well tolerated, with side effects similar to those of CLS and infusion reaction [31]. The number of patients in this report was very small, so a conclusion about the efficacy of this treatment cannot be made, although all patients showed some response.…”
Section: Pediatric Experiencementioning
confidence: 97%
“…Seven of nine evaluable BPDCN patients had major responses, including five CR and two PR after a single course of SL-401 (Frankel et al, 2014). Further clinical and non-clinical evaluations of this immunotoxin (Pemmaraju et al, 2017; Sun et al, 2018) led to its approval by the FDA in 2018 for the treatment of adult and pediatric BPDCN under the name of Tagraxofusp TM (Syed, 2019).…”
Section: Diphtheria Toxin-based Immunotoxinsmentioning
confidence: 99%